2017
DOI: 10.18632/oncotarget.21403
|View full text |Cite
|
Sign up to set email alerts
|

IGF-1R tyrosine kinase inhibitors and Vitamin K1 enhance the antitumor effects of Regorafenib in HCC cell lines

Abstract: The recent RESORCE trial showed that treatment with Regorafenib after Sorafenib failure provided a significant improvement in overall survival in HCC patients. Preclinical and clinical trial data showed that Regorafenib is a more potent drug than Sorafenib. In this study we aimed at improving Regorafenib actions and at reducing its toxicity, by targeting parallel pathways or by combination with Vitamins K (VKs). We investigated the effects of Regorafenib administrated at low concentrations and in combination w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 31 publications
2
20
0
Order By: Relevance
“…IGF-1R is a transmembrane protein with tyrosine kinase activity belonging to the insulin receptor family [34][35][36]. Up-regulation of IGF-1R has been observed in several cancers, including HCC and renal cell carcinoma [37,38]. It has been reported that IGF-1R interacted with the ligand IGF-1 and stimulated PI3K/AKT signaling pathway [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1R is a transmembrane protein with tyrosine kinase activity belonging to the insulin receptor family [34][35][36]. Up-regulation of IGF-1R has been observed in several cancers, including HCC and renal cell carcinoma [37,38]. It has been reported that IGF-1R interacted with the ligand IGF-1 and stimulated PI3K/AKT signaling pathway [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have aimed to improve the actions of systemic drugs and reduce their toxicity, through methods such as targeting parallel pathways or treating in combination with natural compounds [ 19 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to human hepatocarcinoma (HCC), there is evidence showing an enhancement of the 5′-fluorouracil effect on HCC cell lines by CGA treatment, and more recently, Yan et al reported that CGA acts as an effective chemopreventive agent against HCC in both in vitro and in vivo experiments [ 17 , 18 ]. Our previous studies suggested that targeting parallel pathways or combining treatments based on natural compounds could improve the actions of systemic drugs and reduce their toxicity [ 19 ]. Although treatment with the multikinase inhibitor Regorafenib in patients who had HCC progression after Sorafenib failure provided a significant improvement in overall survival, drug toxicity, resistance and subsequent disease relapse are still a problem in HCC management.…”
Section: Introductionmentioning
confidence: 99%
“…Several VKDPs are involved in tumorigenesis [71,84,85] (Table 3). Vitamin K2 administration in vivo inhibits the cellular proliferation of several cancers [96,97]. This led to a number of studies investigating the role of vitamin K intake and supplementation in preventing cancer development, progression and recurrence.…”
Section: Vitamin K In Cancermentioning
confidence: 99%